The mixed oligopoly of cross-border payment systems - Kauko, Karlo; Suomen Pankki (Bank of Finland research discussion papers, 2005)
Tiivistelmä: Maidenvälisten maksujärjestelmien sekaoligopoli.
Keywords: maksujärjestelmät; uusi talous; oligopoli